Hospital Outdoor Spaces: User Experience and Implications for Design. (January 2022) - Tseung, Victrine; Verweel, Lee; Harvey, Martha; Pauley, Tim; Walker, Jan
Objectives: This article aims to describe users' perspectives about the impact of hospital outdoor spaces on the patient experience in a postacute setting. Background: Hospital outdoor space is an important element in healthcare facility design. There is growing evidence that access to green space within hospital outdoor spaces facilitates healing. However, limited studies have explored the users' perspective regarding how hospital outdoor spaces impact the patient experience. Methods: As part of a hospital preoccupancy evaluation, users (patients, family, and staff) were invited to participate in a semi-structured interview to describe their experiences in the hospital's outdoor spaces. Data were analyzed using inductive thematic analysis. Results: Seventy-four individuals participated in this study: 24 inpatients, 15 outpatients, 11 family, 23 staff, and one volunteer. Three themes were identified: (1) outdoor space benefits healing by helping patients focus on life beyond their illness, (2) design of healthcare spaces facilitates patients' access to outdoor space to benefit healing, and (3) programming in the outdoor space promotes healing and recovery. Conclusions: This study describes the users' perspective regarding the value of outdoor spaces and the design elements that influence the patient experience.